2015
DOI: 10.1016/j.sbspro.2015.01.105
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated Learning: Critical-realistic Conceptualization

Abstract: The paper deals with self-regulated learning from the perspective of critical-realistic philosophy. In this respect, it is focused on existing models of self-regulated learning, which it re-conceptualizes through the current categories of critical realism. We draw from the latest works by Bhaskar, Harré and Elder-Vass. Although there has recently been a relatively broad critique of methodology used to evaluate self-regulation, very little space has been devoted to epistemology and ontology. We believe that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In this section, our motivation is presented, as well as the corresponding research questions. Firstly, we are interested in studying the characteristics of the MOOCs used in this research area because prior works suggested that the learning context has a direct influence on self-regulation (Jakešová & Kalenda, 2015). Specifically, this conclusion was reinforced by Ferguson et al (2015) in MOOC environments.…”
Section: Research Questions (Rq)mentioning
confidence: 99%
“…In this section, our motivation is presented, as well as the corresponding research questions. Firstly, we are interested in studying the characteristics of the MOOCs used in this research area because prior works suggested that the learning context has a direct influence on self-regulation (Jakešová & Kalenda, 2015). Specifically, this conclusion was reinforced by Ferguson et al (2015) in MOOC environments.…”
Section: Research Questions (Rq)mentioning
confidence: 99%
“…The lack of such influences may be due to the methodological limitations of this text (and especially the small research sample used). Other individual variables, such as the frequency of using Office suites [52], readiness to learn [53][54][55], and situational factors related to work experience [56], which are difficult to include in the course of a single study due to the limitations of the length of the tool, may also be a limiting factor in the prediction of change in the selected elements of key competences.…”
Section: Discussionmentioning
confidence: 99%
“…For the reason that, implementation of self-Learning in learning can do it and are need on an era of globalization with the source learning it's unlimited. In the application of self-learning, this is not only done as an independent activity in regulated learning [11], but it is more to self-regulation in relation to the understanding of himself so that he can make the best choices for himself. Thus, in the self-learning on this research through are self-evaluation, self-improvement, and self-strengthening it as a stage in understanding and practicing the basic skills taught at school Practice Field at school.…”
Section: A Self-learningmentioning
confidence: 99%